2010
DOI: 10.1590/s1414-81452010000300023
|View full text |Cite
|
Sign up to set email alerts
|

Ambiente hospitalar saudável e sustentável na perspectiva ecossistêmica: contribuições da enfermagem

Abstract: Este texto propõe uma discussão sobre o ambiente hospitalar saudável e sustentável destacando-se as contribuições da enfermagem nesse processo. As bases filosóficas encontram-se ancoradas na teoria ecossistêmica que analisa as sensibilidades necessárias para entender a natureza e os elementos estruturantes do ambiente/espaço hospitalar. Enfatiza-se a força aglutinadora das Unidades Produtivas que, de maneira interdependente e inter-relacionada, devem buscar o espaço sustentável e saudável através da cooperação… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
11
0
1

Year Published

2013
2013
2023
2023

Publication Types

Select...
4
1

Relationship

2
3

Authors

Journals

citations
Cited by 8 publications
(14 citation statements)
references
References 1 publication
0
11
0
1
Order By: Relevance
“…Thus, it is crucial to consider that the biomedical model no longer attains accommodating user needs and what it takes for this to be seen in its entirety, in solidarity, is to converge all efforts to achieve results with regard to healthcare production. This new way of organizing the work process is supported by studies (4)(5)(6)8,(19)(20)(21)(22) which indicate from their findings that we need to understand the healthcare needs better, with the purpose of developing actions for comprehensive healthcare which consider the diversity, the instabilities and complexity of users' demands.…”
Section: Discussionmentioning
confidence: 93%
See 3 more Smart Citations
“…Thus, it is crucial to consider that the biomedical model no longer attains accommodating user needs and what it takes for this to be seen in its entirety, in solidarity, is to converge all efforts to achieve results with regard to healthcare production. This new way of organizing the work process is supported by studies (4)(5)(6)8,(19)(20)(21)(22) which indicate from their findings that we need to understand the healthcare needs better, with the purpose of developing actions for comprehensive healthcare which consider the diversity, the instabilities and complexity of users' demands.…”
Section: Discussionmentioning
confidence: 93%
“…It is observed that the health professionals involved in providing such care are faced with an increasing degree of technical, scientific, affective, integrative and social demands towards health promotion and maintenance in critical and emergency situations. However, the professional relationship in the ICU setting in many health institutions also expressed an organization of mechanical, hierarchical and fragmented work, and has been the point of instability between authors who envision a more flexible, dynamic and cooperative relationship based on dialogue and collective construction, seeking to satisfy the interests and needs of all who are part of that context (6,(17)(18)(19) . The need to change the way of thinking, acting and organizing work should be perceived based on studies and current legislation for ICUs.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…This System Dynamic constantly restructures itself and self-organizes through associations, relationships and interconnections. Thus, the sustainability of the ecosystemic environment, in supporting itself on principles of interdependence, the cyclic flow of resources, cooperation and partnership, constructs itself under different aspects of the same pattern of organization, as the ecosystems are organized, to maximize the sustainability of the space/place/territory 16 . In this complexity, it is relevant to think that the process of change Svaldi JSD, Zamberlan C, Siqueira HCH The ecosystemic approach in nursing/health of a determined reality only becomes possible to happen if the people are capable of recognizing it, reflecting on it, and understand the need for change so as only afterwards to act and transform.…”
Section: The Ecosystemic Approach In Nursing/healthmentioning
confidence: 99%